Competitive formation of DNA linkage isomers by a trinuclear platinum complex and the influence of pre-association. Issue 8 (19th November 2014) - Moniodis, Joseph J.; Thomas, Donald S.; Davies, Murray S.; Berners-Price, Susan J.; Farrell, Nicholas P.
Abstract : The trinuclear platinum drug BB3464 pre-associates in the minor groove at two different sites on a 14-mer duplex and this dictates the nature of the adducts formed in both 5′-5′ and 3′-3′ directions. Abstract : 2D [ 1 H, 15 N] HSQC NMR spectroscopy has been used to monitor the reaction of fully 15 N-labelled [ trans -PtCl(NH3 )2 2 (μ- trans -Pt(NH3 )2 NH2 (CH2 )6 NH2 2 )] 4+ (BBR3464 ( 15 N-1 )) with the 14-mer duplex (5′-d(ATACATG(7)G(8)TACATA)-3′·5′-d(TATG(18)TACCATG(25)TAT)-3′ orI ) at pH 5.4 and 298 K, to examine the possible formation of 1, 4 and 1, 5-GG adducts in both 5′-5′ and 3′-3′ directions. In a previous study, the binding of the dinuclear 1, 1/ t, t toI showed specific formation of the 5′-5′ 1, 4 G(8)G(18) cross-link, whereas in this case a mixture of adducts were formed. Initial 1 H NMR spectra suggested the presence of two pre-associated states aligned in both directions along the DNA. The pre-association was studied in the absence of covalent binding, by use of the "non-covalent" analog [ trans -Pt(NH3 )3 2 (μ- trans -Pt(NH3 )2 NH2 (CH2 )6 NH2 2 )] 6+ (AH44, 0 ). Chemical shift changes of DNA protons combined with NOE connectivities between CH2 and NH3 protons of0 and the adenine H2 protons onI show that two different molecules of0 are bound in the minor groove. Molecular dynamic simulations were performed to study the interaction of0 at the two pre-association sites using charges derived from density functional theory (DFT) calculations. Structures where the central platinum is located in the minor groove and the aliphatic linkers extend into the major groove, in opposite directions, often represent the lowest energy structures of the snapshots selected. In the reaction of 15 N-1 andI, following the pre-association step, aquation occurs to give the mono aqua monochloro species2, with a rate constant of 3.43 ± 0.03 × 10 −5 s −1 . There was evidence for two monofunctional adducts (3, 4 ) bound to the 3′ (G8) and 5′ (G7) residues and the asymmetry of the 1 H, 15 N peak for3 suggested two conformers of the 3′ adduct, aligned in different directions along the DNA. The rate constant for combined monofunctional adduct formation (0.6 ± 0.1 M −1 ) is ca. 2-fold lower for1 compared to 1, 1/ t, t, whereas the rate constant for conversion of the combined monofunctional species to combined bifunctional adducts (5 ) (8.0 ± 0.2 × 10 −5 s −1 ) is two-fold higher.